Mesozooplankton abundance and biomass during Alkor cruise AL544 (WP2 net) - Helena Hauss; Cornelia Jaspers (PANGAEA, 2023)
A key goal of the AL544 cruise in September 2020 in the Baltic Sea was to enhance our understanding of environmental and zooplankton (especially gelatinous) population fluctuations along an east-west transect. Vertically integrated mesozooplankton abundance and diversity was obtained from plankton net hauls followed by image analysis. Samples were collected using a Hydrobios standard WP2 net (200μm) vertical from bottom to surface. Samples were scanned using an Epson V750 Pro flatbed scanner at 2400dpi, scanned as one size fraction, split sometimes multiple times. Processed using ZooProcess. Image data are available on https://ecotaxa.obs-vlfr.fr/prj/5189 and were sorted into taxonomic categories (examples in AL544_mesozoo_examples.zip). Using the export file (.tsv) individual biomass was calculated based on object area and taxonomic identity according to Lehette and Hernandez-Leon (2009). Abundance and biomass are then aggregated to concentrations (per volume).